Simulation von Fahrspielen und Energieflüssen in Nahverkehrssystemen - Kühn, Christoph (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2018)
For ecological und economic reasons, special attention is paid to the energy balance of rail-bound, local, direct current-based transport systems. With the tram and urban railway network of Karlsruhe being used as an example, 16 simulation scenarios with different measures for energy optimization are analysed in a coupled computation of driving cycles and energy flows.